2012
DOI: 10.1088/0004-637x/746/1/95
|View full text |Cite
|
Sign up to set email alerts
|

The Integrated Stellar Content of Dark Matter Halos

Abstract: Measurements of the total amount of stars locked up in galaxies as a function of host halo mass contain key clues about the efficiency of processes that regulate star formation. We derive the total stellar mass fraction f ⋆ as a function of halo mass M 500c from z = 0.2 to z = 1 using two complementary methods. First, we derive f ⋆ using a statistical Halo Occupation Distribution model jointly constrained by data from lensing, clustering, and the stellar mass function. This method enables us to probe f ⋆ over … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

55
375
7
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 248 publications
(438 citation statements)
references
References 111 publications
55
375
7
1
Order By: Relevance
“…We also compare our results with the recently published average groups' stellar mass fractions by Leauthaud et al (2012): these authors constrain the fraction of stars in group-sized haloes 3 Note that these values cannot be directly compared with those in Fig. 11 since those are computed by integrating the mass function down to a different stellar mass.…”
Section: The Average Stellar Mass Fraction In Groupsmentioning
confidence: 82%
“…We also compare our results with the recently published average groups' stellar mass fractions by Leauthaud et al (2012): these authors constrain the fraction of stars in group-sized haloes 3 Note that these values cannot be directly compared with those in Fig. 11 since those are computed by integrating the mass function down to a different stellar mass.…”
Section: The Average Stellar Mass Fraction In Groupsmentioning
confidence: 82%
“…The abundancematching and weak lensing studies (e.g., Moster et al 2010;Behroozi et al 2010;Leauthaud et al 2012) suggest that these halos host central galaxies with a stellar mass of ∼10 11 M . At this stellar mass, the mass quenching is efficient according to Peng et al (2010), and both passive and star-forming galaxies are observed in the low-z Universe (e.g., Baldry et al 2012;Ilbert et al 2013).…”
Section: The Future Of Z ∼ 2 Populationsmentioning
confidence: 98%
“…Finally, weak gravitational lensing can also provide strong constraints on the characteristic halo mass hosting a galaxy population (e.g., Mandelbaum et al 2006). Leauthaud et al (2012) made a combined analysis of z < 1 galaxies combining all these techniques and strongly constrained the M − M h relation. However, only a few studies extended these results at higher redshift.…”
Section: Introductionmentioning
confidence: 99%
“…Tinker et al 2013). The details of the SHMR-based model 3 that we use and how it is constrained from COSMOS data are described in Leauthaud et al (2011Leauthaud et al ( , 2012b. Other models based on the conditional SMF or abundance matching techniques would also our purpose (e.g.…”
Section: E T H O D O L O G Ymentioning
confidence: 99%